Encouraging coercive control: militarisation and classical crowd theory in Turkish protest policing - Atak, Kıvanç (Policing and society, 2017)
The coercive character of protest policing is a tangible problem in Turkey. Since the resurgence of contentious politics from the late 1980s, major issues in protest policing have been officially recognised, and eventually addressed by public authorities with an agenda of reform. However, the excessive use of force by the police, even in the face of predominantly peaceful protests, lingered on well into the past decade, leaving behind dozens of dead citizens and thousands injured. In this article, I consult two main concepts, militarisation and police knowledge, to understand the institutional factors that underpin the repressive policing practices in Turkey. Among the different aspects of militarisation, I am particularly interested in the proliferation and adoption of less-lethal weapons in the strategies of protest control, while by police knowledge, I largely refer to the role of crowd theory in shaping the mind-set of the police and their behaviour on the street. Drawing on the theoretical debates in the literature and a variety of empirical sources, I argue that the growing reliance on less-lethal weapons, on the one hand, and police knowledge conditioned by classical crowd theory, on the other, encourage, if not propel, coercive styles of policing at public protests in Turkey.